A proposed design of an undergarment for women with scoliosis - Villanueva, Eva Caparas; Mayo, Adelaida Villaraza (2000.)
The study is about proposing a prototype brassiere for women with scoliosis. Participants were selected purposively. The researcher used the Quasi-Experimental research design because participants were not selected at random. This design consists of two groups: Experimental design consists of two groups: experimental Group A and Control Group B. Only group A have worn the modified brassieres at least four days within one week while Group B observes the performance of their ordinary brassieres. The age of the participants are 22 to 28 years old. The total number of participants were eight females: seven with Right Thoracic and one Right Thoracolumbar Scoliosis. They were divided equally at random into two groups. Both groups were given pretest questions to identify their preferences in selecting brassieres that fits well. The posttest were given after one week. It included their evaluation on the performance of the brassieres. The Likert Scale was used in measuring the responses both on the pretest and posttest. Frequency Distribution and percentage methods was used to analyze the data obtained. The modified brassiere will be more convenient for women with 30 and above degrees of curvature. In Group A, there was a positive response of acceptance of our modified brassiere which consists of two participants with 32, one 29 and one 22 degrees of curvature. The velcro adjustments offered more alternative on the tightness of bra on the hump area as rated by our participants. It was also evident that the velcro was able to give ease for the participants in group A. Both groups were not ready to have a special brassiere in which physical attractiveness of the bra are more important than fit. However, the response of our participants on the performance of the modified brassiere showed that it is suitable for women with scoliosis.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Brassieres; Underwear